1971
DOI: 10.1002/jlcr.2590070304
|View full text |Cite
|
Sign up to set email alerts
|

The non‐metabolite residue a limitation to the tracer method

Abstract: SUMMARYThe occurrence of non-metabolite residues from labeled drugs administered to animals is discussed. Selected are 14C-labeled thiabendazole, nitroglycerine, nortriptyline, amitryptiline, p-dimethylaminobenzene, nihydrazone and ronidazole. The rapid degradation which is responsible for the phenomenon requires that all tracer applications in living systems be accompanied by a demonstration of ihe biological stability of the parent con+pound,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…After 1 week a plateau (Tables II and III) in the concentration of nonpolar "metabolites" was reached, which would suggest either a steady state for product formation-degradation (unlikely due to the rapid depletion of methoprene) or that the nonpolar "metabolites" are relatively stable to further catabolism. Subsequent gel permeation chromatographic (gpc) separation of these extracts showed considerable radiolabel (56-70% of nonpolar metabolites) present in high molecular weight bands corresponding to natural plant constituents, i.e., nonmetabolite residues (Rosenblum et al, 1971). It is suggested that the peak in nonpolar "metabolite" concentration (Tables II and , 3 days for alfalfa and 1 day for rice) represents a maximum for primary metabolites (i.e., 2-7).…”
Section: Resultsmentioning
confidence: 99%
“…After 1 week a plateau (Tables II and III) in the concentration of nonpolar "metabolites" was reached, which would suggest either a steady state for product formation-degradation (unlikely due to the rapid depletion of methoprene) or that the nonpolar "metabolites" are relatively stable to further catabolism. Subsequent gel permeation chromatographic (gpc) separation of these extracts showed considerable radiolabel (56-70% of nonpolar metabolites) present in high molecular weight bands corresponding to natural plant constituents, i.e., nonmetabolite residues (Rosenblum et al, 1971). It is suggested that the peak in nonpolar "metabolite" concentration (Tables II and , 3 days for alfalfa and 1 day for rice) represents a maximum for primary metabolites (i.e., 2-7).…”
Section: Resultsmentioning
confidence: 99%
“…A correct choice of the labelling position could be verified by means of the colour reaction revealing the aminosuifonyl group and indicating the presence of only drugrelated metabolites (22). Unlabelled metabolites, none of which were detected in the present study, were undoubtedly rare since only the N-dealkylation in metabolite VI could cause the loss of an unlabelled pyrrolidine moiety, which would probably be the N-ethyl-lmethanal-pyrrolidine.…”
Section: Discussionmentioning
confidence: 91%
“…The quantitative importance of acetate production from bovine metabolism of 1 implies that methoprene is metabolized as a methyl-branched fatty acid "food" in addition to being detoxified and excreted like most xenobiotics. The degradation of 1 to natural "nonmetabolite residues" (Figure 4) (Rosenblum et al, 1971) is indicative of extensive biodegradability. The production of nonmetabolite residues (i.e.…”
Section: Resultsmentioning
confidence: 99%